FACIAL OVERFILLED SYNDROME: A REVIEW OF PATHOGENESIS, CLINICAL PRESENTATION AND MANAGEMENT - Katarzyna Skibicka; Joanna Kryślak; Szymon Szabelski; Adam Solarz; Estera Graczyk; Maciej Sokołowski; Karolina Oskroba; Jakub Filip Turcza (International Journal of Innovative Technologies in Social Science, 2025)
Facial overfilled syndrome is becoming an increasingly common complication in the field of aesthetic medicine. It may result from repeated and excessive filler injections, the use of improperly selected products, or their placement in inappropriate areas of the face. Although fillers are generally considered safe, their use can lead to a variety of complications. To prevent and manage potential issues, it is crucial that practitioners performing these procedures fully understand the extent and types of adverse events that may occur. This article provides a review of current literature on the concept of facial overfilled, including its pathogenesis, clinical presentation, and treatment options.Objective: To review selected articles, literature and recent reports on the pathogenesis, clinical presentation and treatment of facial overfilled syndrome (FOS).Material and Methods: A literature review from PubMed and Google Scholar.